Science in the Context of Culture and Science as a Phenomenon of Culture - Gevorgyan, Hamlet (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
In this paper, the proposition is stated and the argument is withdrawn that the essential characteristic trait of scientific knowledge is its objectivity, that is, its consideration as an abstract idea, i.e., as an idea alienated of personal subject, free from personal prejudices, of its expectations and assumptions. In this, Aristotlean, position, the discursive reason is dealing with external facts, and, in this case, the process of stating certain assertions (including a number of theoretical statements), their argumentation, their admission or negation, – become communicable (communicative), understood synonymously, “intelligible for every individual subject, endowed with ration”, as it is formulated by Immanuel Kant.